Comparing efficacy of Rifaximin plus Lactulose vs. Lactulose alone in treating Hepatic Encephalopathy - Tanveer Hussain, Misbah Sattar, Sara Mustafa, Uzma Batool, Shafqat Iqbal, Binish Hassan, Tanveer Hussain, Misbah Sattar, Sara Mustafa, Uzma Batool, Shafqat Iqbal, Binish Hassan (Journal of Rawalpindi Medical College, 2020)
Background: Hepatic Encephalopathy is a syndrome observed in patients with liver cirrhosis. Various treatment modalities are in use for treatment of Porto Systemic Encephalopathy (PSE). Our study aimed to compare the efficacy of Rifaximin plus Lactulose vs.Lactulose alone in treating Hepatic Encephalopathy in local population. Materials & Methods: The study was conducted at a tertiary care hospital recruiting decompensated chronic liver disease(DCLD) patients with PSE. Using simple random sampling, patients were divided in two groups (A & B). Patients in group A received Lactulose plus Rifaximin while group B received Lactulose alone. Efficacy of treatment was assessed as return of the conscious level to pre-encephalopathy state as per clinical examination within 1 week after start of the treatment. Results: A total of 124 patients were included in the study with each group (A & B) containing 62 patients. Frequency and percentage of efficacy among group A (Rifaximin plus Lactulose) verses group B (Lactulose alone) in treating Hepatic encephalopathy was 45 (72.6%) and 32 (51.6%) respectively. Conclusion: The study concluded that there is a significant difference in proportions of patients showing complete recovery from Hepatic encephalopathy treated with Lactulose plus Rifaximin as compared to Lactulose alone.